POSSIBILITIES OF MODERN PHYSICAL METHODS OF ANTISEPSIS IN THE TREATMENT OF ACUTE LUNG ABSCESSES IN PATIENTS WITH DIABETES MELLITUS - Khamdamov, Sh.A.; Abdurakhmanov, F.M.; Bobokulova, Sh.A.; Korikhonov, D.N.; Okhunov, A.O.; Boboev, K. Kh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Increasing the effectiveness of treatment of lung abscesses is an urgent problem of thoracic surgery in connection with the increase in the contingent of patients with respiratory diseases, an increase in the number of complications and adverse outcomes of purulent-destructive diseases of the lungs and pleura. Material. The clinical study is based on the results of the treatment of 107 patients with acute lung abscesses against the background of diabetes mellitus. Patients were examined and treated in the surgical infection department of the Multidisciplinary Clinic of the Tashkent Medical Academy from 2002 to 2022 years. Results. The high effect of the use of vacuum therapy in the rehabilitation of lung abscesses has a pronounced positive effect. The results are confirmed by the analysis of clinical signs in the process of transthoracic sanitation of lung abscesses, the identification of differences in the manifestation of detoxification, anti-inflammatory and immunoprotective effects in comparison with the results of fibrobronchoscopy, ultrasound and volume measurements introduced and excreted during the sanitation of liquids. Conclusion. Rehabilitation of foci of destruction with the help of controlled negative pressure allowed to improve clinical outcomes with a high severity index of the disease in patients with acute lung abscesses against the background of diabetes mellitus.